An Analysis of Directive Speech Acts By Main Character In “Ke Jogja” Short Movie - Rizki, Lalu Satya Imam; Syamsurrijal, Syamsurrijal; Suktiningsih, Wiya (CV Insan Kreasi Media, 2023)
The aim of this study is to identify the types of directive speech used by the main character in the short film